PEMBELAJARAN MATEMATIKA REALISTIK BERBASIS BUDAYA LOKAL UNTUK MENINGKATKAN RELEVANSI DAN MINAT BELAJAR SISWA SEKOLAH DASAR - Damanik, Putri Adhelia Br; Purba, Nazwi Haliza; Rahmayani, Rahmayani; Saragih, Doni Irawan; Syahrial, Syahrial (Universitas Negeri Medan, 2025)
This study aims to examine the utilization of local cultural contexts in realistic mathematics learning to enhance the relevance and learning interest of elementary school students. The background of this research is the low level of students’ engagement and the lack of contextual relevance in mathematics learning, which often causes students to perceive mathematics as abstract and disconnected from their daily lives. This study employed a qualitative approach using a literature review method by analyzing various relevant sources, including national and international journal articles, books, and research reports published within the last ten years. The results of the analysis indicate that the integration of local cultural elements in realistic mathematics learning can make learning more meaningful, contextual, and engaging for students. Cultural contexts help students understand mathematical concepts through real-life experiences that are familiar to them, thereby increasing motivation and interest in learning. In addition, realistic mathematics learning based on local culture supports the development of students’ critical thinking skills and strengthens their appreciation of local values. Therefore, the application of local culture-based realistic mathematics learning is considered an effective strategy to improve the relevance and learning interest of elementary school students.